Raw Material Inventory Calculation Analysis Using Fifo And Average Methods In Determining Cost Of Cost Of Sold - Sarah, Alya (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2023)
The purpose of this study aims to Analysis of Raw Material Inventory Calculations Using the FIFO and Average Methods in Determining Cost of Goods Sold. Inventory calculations really need to be done by the organization to find out how much inventory it has. In this study aims to find out how to compare inventory calculations using the FIFO and Average methods in determining the cost of goods sold. The research method used is descriptive qualitative method with data collection techniques using participatory observation methods, interviews, documentation, triangulation, as well as secondary data and primary data. The results of the researcher's discussion can be concluded that the cost of goods calculated using the FIFO method produces a higher cost of goods sold compared to the Average method. The final value of the inventory will affect the profit that will be generated later. The Average method will produce a lower cost of goods sold than the FIFO method which will result in a higher net profit than the FIFO method.